The mycoremediation potential of the armillarioids: a comparative genomics analysis - Champramary, Simang; Indic, Boris; Szűcs, Attila; Tyagi, Chetna; Languar, Omar; Hasan, K. M. Faridul; Szekeres, András; Vágvölgyi, Csaba; Kredics, László; Sipos, György (Frontiers in Bioengineering and Biotechnology, 2023)
Genes involved in mycoremediation were identified by comparative genomics analysis in 10 armillarioid species and selected groups of white-rot Basidiomycota (14) and soft-rot Ascomycota (12) species to confine the distinctive bioremediation capabilities of the armillarioids. The genomes were explored using phylogenetic principal component analysis (pPCA), searching for genes already documented in a biocatalysis/biodegradation database. The results underlined a distinct, increased potential of aromatics-degrading genes/enzymes in armillarioids, with particular emphasis on a high copy number and diverse spectrum of benzoate 4-monooxygenase [EC:1.14.14.92] homologs. In addition, other enzymes involved in the degradation of various monocyclic aromatics were more abundant in the armillarioids than in the other white-rot basidiomycetes, and enzymes involved in the degradation of polycyclic aromatic hydrocarbons (PAHs) were more prevailing in armillarioids and other white-rot species than in soft-rot Ascomycetes. Transcriptome profiling of A. ostoyae and A. borealis isolates confirmed that several genes involved in the degradation of benzoates and other monocyclic aromatics were distinctively expressed in the wood-invading fungal mycelia. Data were consistent with armillarioid species offering a more powerful potential in degrading aromatics. Our results provide a reliable, practical solution for screening the likely fungal candidates for their full biodegradation potential, applicability, and possible specialization based on their genomics data.